The distribution of wealth in Spain and the USA: The role of socioeconomic factors - Pedro Salas-Rojo; Juan Gabriel Rodríguez (SERIEs - Journal of the Spanish Economic Association, 2021)
The literature has typically found that the distribution of socioeconomic factors like education, labor status and income does not account for the remarkablewealth inequality disparities between countries.As a result, their different institutions and other latent factors receive all the credit. Here,we propose to focus on one type of wealth inequality, the inequality of opportunities (IOp) in wealth: the share of overall wealth inequality explained by circumstances like inheritances and parental education. By means of a counterfactual decomposition method, we find that imposing the distribution of socioeconomic factors of the USA into Spain has little effect on total, financial and real estate wealth inequality. On the contrary, these factors play an important role when wealth IOp is considered. A Shapley value decomposition shows that the distribution of education and labor status in the USA consistently increase wealth IOp when imposed into Spain, whereas the opposite effect is found for the distribution of income.
Keywords: C81; D31; D63; 330; Wealth inequality; Socioeconomic factors; Inequality of opportunity; Spain; USA